Observational and behavioural equivalences for soft concurrent constraint programming - Gadducci, Fabio; Santini, Francesco; Pino, Luis F.; Valencia, Frank D. (Journal of logical and algebraic methods in programming, 2017)
We present a labelled semantics for Soft Concurrent Constraint Programming (SCCP), a meta-language where concurrent agents may synchronise on a shared store by either posting or checking the satisfaction of (soft) constraints. SCCP generalises the classical formalism by parametrising the constraint system over an order-enriched monoid, thus abstractly representing the store with an element of the monoid, and the standard unlabelled semantics just observes store updates. The novel operational rules are shown to offer a sound and complete co-inductive technique to prove the original equivalence over the unlabelled semantics. Based on this characterisation, we provide an axiomatisation for finite agents.